The pros and cons of getting engaged in an online social community embedded within digital cognitive behavioral therapy for insomnia: survey among users - Coulson, Neil S.; Smedley, Richard; Bostock, Sophie; Kyle, Simon D.; Gollancz, Rosie; Luik, Annemarie I.; Hames, Peter; Espie, Colin (Journal of Medical Internet Research, 2016)
Background: Sleepio is a proven digital sleep improvement programme based on cognitive behavioural therapy (CBT) techniques. Users have the option to join an online community that includes weekly expert discussions, peer-to-peer discussion forums and personal message walls. Objective: The aims of this study were to (1) explore the reasons for deciding to engage with the Sleepio online community, (2) explore the potential benefits arising from engagement with the online community, (3) identify and describe any problematic issues related to use of the online community. Methods: In total, 100 respondents (70% female; mean age 51, range 26-82 years) completed the online survey. Most respondents had started Sleepio with chronic sleep problems (59% to to 10 years, 35% >10years), and had actively engaged with the online community (85% had made a discussion or wall post). At the time of the survey, respondents had used Sleepio for a median of 12 weeks (range from 3 weeks to 2 years). Results: Responses to the open-ended questions were analysed using thematic analysis. This analysis revealed five initial drivers for engagement including: 1) the desire to connect with people facing similar issues; 2) seeking personalised advice; 3) curiosity; 4) being invited by other members; and 5) wanting to use all available sleep improvement tools. Advantages of engagement included: access to continuous support, reduced sense of isolation, being part of a non-judgmental community, personalised advice, positive comparisons with others, encouragement to keep going, and altruism. Five potential disadvantages were: design and navigation issues, uncertain quality of user-generated content, negative comparisons with others, excessive time commitments, and data privacy concerns. Participants related their community experiences to engagement with the Sleepio programme with the many stating it had supported their efforts to achieve sleep improvement, as well as helping with adherence and commitment to the programme. Conclusions: Despite some concerns, members regarded the Sleepio community as a valuable resource. Online communities may be a useful means through which to support long-term engagement with online therapy for insomnia.